Pengaruh Perceived Ease of Use dan Perceived Security Terhadap Customer Loyalty Melalui Customer Trust pada Aplikasi Bank Digital - Hendryawan Cipta Mulia; Ryna Parlyna; Inkreswari Retno Hardini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Customers use of banking services is changing as a result of the growth of digital banking in Indonesia. Customer loyalty is essential to the long-term viability of digital banking use due to the increasingly intense competition. The purpose of this study is to examine how customer loyalty is impacted by perceived security and perceived ease of use, using customer trust as a mediating factor among users of the XYZ Bank application. Data were collected through questionnaires distributed to 150 university students in East Jakarta who are active users of the XYZ Bank application. Structural Equation Modeling based on Partial Least Squares (SEM-PLS) was the data analysis method employed. The findings demonstrate that customer loyalty and customer trust are positively and significantly impacted by perceived security and perceived ease of use. Furthermore, it has been demonstrated that customer trust increases customer loyalty and can moderate the impact of perceived security and perceived ease of use on customer loyalty.